Organizacje dziennikarskie w Łodzi (1916-1939) - Olejnik, Leszek (Acta Universitatis Lodziensis. Folia Historica, 1999)
The first organization of journalists in Poland – the Association of the Mutual Help of the Polish Journalists – was created in Lwów in 1893. It was followed by the similar organizations in the other towns later. Still it was in Łódź not earlier but in August 1916 where the Association of the Polish Writers and Journalists was created and maintained its activity till 1919. The association of a similar character of mutual help was organized as well among the Jewish journalists in 1918 and was named the Association of the Jewish Writers and Journalists. The first full professional organization of the press editorial staff in Łódź was the Syndicate of the Polish Journalists, which came into being in April 1921. Its cofounder and the first president was editor Lucjan Dąbrowski. This organization has displayed its activity since 1924, when it became a part of the all-Polish journalist association. Since 1927 the journalists from the Jewish and German press in Łódź were also associated in that organization, which changed a name and then was called the Syndicate of the Journalists of Łódź (SDŁ). For many years (since 1924 till 1939) its president was editor Czesław Gumowski. The Syndicate dealt not only with the material and moral interests of its members. It also participated in the nation-wide actions, and spread wide cultural and entertainment activity as well (among the others the so called Press Reduts [Reduty Prasy] was organized – it ws a kind of the public press fetes). In Łódź in the years of the Second Republic of Poland (1918-1939) existed as well: the Union of the Sport Journalists of Republic of Poland and the Association of the Polish Journalists and Publicists of Economy.